Malaysian ESL students` syntactic accuracy in the usage of English modal verbs in argumentative writing. - Mukundan, Jayakaran; Saadullah, Khairil Anuar; Ismail, Razalina; Jusoh Zasenawi, Nur Hairunnisa (Canadian Center of Science and Education, 2013)

(untitled)
This research studied the use of modals in argumentative written tasks by Form 5 Malaysian secondary school ESL students. The aim of this study was to examine the use of English modals at the syntactic level from data presented in the MCSAW Corpus. The research design comprised a qualitative technique through discourse analysis aided by descriptive statistics from a concordance, which was utilized to identify the modal verbs used by the Form 5 level in Malaysian schools. The research findings showed that Malaysian students had little problem using modal verbs grammatically in argumentative writing. It was also found that Malaysian students preferred to use a lot of modals in their writings. However, the use of these modals was limited to a few words only. It was concluded that despite the inaccuracies in terms of meanings, most students were able to use syntactically accurate modals in their sentences. Several recommendations are proposed with the aim of improving the teaching of modal verbs in Malaysian schools.